Rumah Tahfiz and the Dynamics of Local Islamic Civilization: An Analysis of Community Engagement in Strengthening Quranic Education in Palembang - Uri Safitri; Uswatun Hasanah; Muhammad Noupal; Mohammad Syawaludin; Agus Rifqi Ridwan; Davik bin Muhammad Yasin (ZAD Al-Mufassirin, 2026)
This research is motivated by the development of Rumah Tahfiz as a community-based Qur’an education institution that has a strategic role in strengthening Islamic values and the dynamics of local Islamic civilization in Palembang City. This study aims to analyze the development of Rumah Tahfiz  within the dynamics of local Islamic civilization in Palembang City, identify forms of community involvement in strengthening Qur’an education, and explain the factors that influence community participation in Rumah Tahfiz . This study uses a qualitative approach with a descriptive-analytical method. The research results show that community involvement in supporting Rumah Tahfiz  is realized through financial support, provision of facilities and infrastructure, participation in social-religious activities, as well as strengthening community-based religious environments. The novelty of this research lies in the analysis of the relationship between Rumah Tahfiz, community participation, and the dynamics of local Islamic civilization in the context of the urban Malay-Islamic society in Palembang. This study positions Rumah Tahfiz  not only as a non-formal educational institution but also as a socio-religious institutions that play a role in the development of local Islamic civilization.